FRI0017 An exploratory study on the role of vitamin d supplementation in improving pain and disease activity in rheumatoid arthritis. (12th June 2018) - Adami, G.; Viapiana, O.; Bogliolo, L.; Cantatore, F.P.; Varenna, M.; Malavolta, N.; Del Puente, A.; Muratore, M.; Orsolini, G.; Gatti, D.; Rossini, M.; ,
Abstract : Background: Lower serum vitamin D levels have been associated with various autoimmune disorders. Especially in patients affected by Rheumatoid Arthritis (RA), has been observed an inverse correlation between serum levels of 25-hydroxyvitamin D (25OHD), pain and disease activity, but the cause-effect relationship is not clear. Objectives: The aim of this exploratory study is to investigate the effects of supplementation with cholecalciferol (vitD3) in improving pain and disease activity in RA patients with or without vitamin D deficiency (25OHD<20 ng/ml). Methods: In this prospective open-label intervention study, patients fulfilling the EULAR/ACR 2010 criteria for diagnosis of RA, in non-remission (DAS28-CRP>2, 6), on stable disease-modifying antirheumatic drugs, and whose treatment was not expected to be changed over a 3 month period following inclusion, were recruited. DAS28-CRP, VAS pain and serum levels of 25OHD, were evaluated at the baseline and after 3 months of supplementation with oral 100, 000 IU/monthly of vitD3. Results: A sample composed by 61 patients (47 females), with an average age (SD) of 5812 years within 26–86 years range were included. At baseline the mean (SD) 25OHD levels were 2210 ng/mL. 57% of the patients were found to have vitamin D deficiency (<20 ng/mL). Mean serum 25OHD levels improved from 13±5 to 32±12 and from 29±7 to 41±10 ng/mL in patients with or without vitamin D deficiency, respectively. At baseline, mean VAS pain was significantly higher in patients with vitamin D deficiency. In the figure are shown DAS28-CRP and VAS pain at baseline and after 3 months of vitD3 supplementation both in patients with or without vitamin D deficiency. After large doses of VitD3, VAS pain significantly decreased in patients with vitamin D deficiency, while DAS28-CRP significantly improved only in patients without vitamin D deficiency at baseline. Conclusions: VitD3 supplementation appears to be associated with significant and different effects on pain and disease activity in RA patients dependent on 25OHD serum levels. Vitamin D deficiency (<20 ng/mL) seems to be mainly correlated with pain, while higher levels of 25OHD might have immunomodulatory effects. A randomised, double-blind, low versus high vitD3 dose, placebo-controlled trial is recommended. Disclosure of Interest: None declared